Transcriptomic Analysis Reveals a Sex-Dimorphic Influence of GAT-2 on Murine Liver Function - Fu, Jian; Zhang, Qingzhuo; Wu, Zebiao; Hong, Changming; Zhu, Congrui (Frontiers in Nutrition, 2021)
Accumulating evidence shows that the γ-amino butyric acid (GABA)ergic system affects functions of different organs，and the liver is one of the most sex-dimorphic organs in animals. However, whether and how GABAergic system influences liver function in a sex-specific manner at intrinsic molecular level remains elusive. Here, firstly, we find that the levels of GABA are significantly increased in the livers of female mice with GABA transporter (GAT)-2 deficiency (KO) while it only slightly increased in male GAT-2 KO mice. Apart from the amino acids profiles, the expressions of toll-like receptors (TLRs) also differ in the livers of female and male KO mice. Moreover, RNA-seq results show 2,227 differentially expressed genes (DEGs) in which 1030 that are up-regulated while 1197 that are down-regulated in the livers of female KO mice. Notably, oxidative phosphorylation, non-alcoholic fatty liver disease (NAFLD), Huntington’s disease, and peroxisome proliferator-activated receptor (PPAR)signaling pathways are highly enriched by GAT-2 deficiency, indicating that these pathways probably meditate the effects of GAT-2 on female liver functions. On the other hand, only 1,233 DEGs including 474 that are up-regulated and 759 that are down-regulated in the livers of male KO mice. Interestingly, retinol metabolism, PPAR signaling pathway, and tuberculosis pathways are substantially enriched by GAT-2 deficiency, suggesting that these pathways may be responsible for the effects of GAT-2 on male liver functions. Collectively, our results reveal the sex-dimorphic effects of GAT-2 in guiding liver functions, and we propose that targeting GABAergic system (e.g., GATs) in a sex-specific manner could provide previously unidentified therapeutic opportunities for the liver diseases.